Implicações da OCPC 07 no disclosure e na forma das notas explicativas das demonstrações contábeis - Silva, Régis Barroso (2017)
The purpose of the financial statements is to provide useful information about a financial position and the performance of companies. In this context, the notes are fundamental, as they clarify quantitative information presented in the financial resources and addition of qualitative elements linked to the decision-making process. Recent concerns have arisen about the fact that accounting statements are becoming bigger and more expensive for a company, because, over time, the accumulation of disclosure requirements has occurred, without a review of its usefulness and materiality, directly affecting an informational quality. Given these discussions and in order to align Brazilian accounting principles with the international standard of disclosure, in 2014, the Accounting Pronouncements Committee (CPC) issued technical guideline OCPC 07, which deals with the basic elaboration and disclosure requirements that must be observed by the entities when disclosing financial reports, specifically in relation to the information contained in the notes. The present study proposes to contribute to enrich the literature on materiality and disclosure, demonstrating how companies have reacted to the growing movement that seeks to disseminate quality to the market. The research aims to study the behavior of Brazilian companies in the face of the current disclosure guidelines established by the regulatory entities, considering the form of their notes and their level of disclosure in view of the publication of OCPC 07. For this purpose, companies in the processed food segment listed on BM&FBovespa, with data for the years 2010 to 2016. The format of the explanatory notes was submitted to content analysis, considering the categories size, readability and similarity. The level of disclosure was calculated for the standards that address material economic facts, based on the perception of the market analysts that accompany the companies in the sample. The statistical treatment of the data contemplates the use of test of average, linear regression and analysis of clusters. The results obtained showed that, with respect to the form of the notes, when comparing the periods before and after OCPC 07, there were significant changes only in the readability of the analyzed documents and in relation to the disclosure, there were no changes that could be attributed to OCPC 07. It was identified that the companies issuing ADR, participants in the Novo Mercado and audited by Big Four, have a larger size of notes in relation to other companies, due to the greater enforcement by international regulatory agencies, corporate governance practices in addition to those required by law and the standardization of notes by audit firms through the disclosure of a model note. It was noticed that the time of initial public offering is inversely associated with the size of these documents, providing evidence that the know-how acquired contributes to the learning curve of the companies, causing only relevant aspects to be disclosed to the stakeholders. In a general analysis, it was observed that OCPC 07 still has no impact on the quality of accounting information within the companies in the processed food segment.